2014
DOI: 10.1515/jpem-2013-0286
|View full text |Cite
|
Sign up to set email alerts
|

Age of thelarche and menarche in contemporary US females: a cross-sectional analysis

Abstract: Aim A recent secular trend towards earlier thelarche has been suggested. The aim of this study is to examine normative ages of thelarche and menarche in contemporary US females. Methods Trained physicians documented Tanner breast stage by observation in a cross-sectional cohort. Age of menarche was self-reported. The subjects were healthy female children and adolescents. The mean age of thelarche was determined by probit analysis and the mean age of menarche was determined by using a normal time-to-event mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 14 publications
(29 reference statements)
11
44
1
Order By: Relevance
“…The girls who were in a more advanced Tanner stage of breast development were older. This finding, as in most other studies, was statistically significant, [10,11,23] suggesting a linear relationship between sexual maturity and chronological age in a normal setting.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The girls who were in a more advanced Tanner stage of breast development were older. This finding, as in most other studies, was statistically significant, [10,11,23] suggesting a linear relationship between sexual maturity and chronological age in a normal setting.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, researchers in SA [28] reported a stable onset of puberty (age of breast budding ranging between 9.8 -10.5 years) for 10 -15 years and a significant secular trend in menarche, with an average decline of 0.5 years/decade for urban black SA girls, suggesting that the tempo of pubertal maturation is increasing in girls born in the Soweto-Johannesburg area. [28] Their finding contrasts with those of most other studies [10,11,23] that have reported a significant secular trend in breast development and stable mean age at menarche over several decades, suggesting the end of the secular trend for menarche. Our study did not show pubertal onset below 8 years nor above 13 years of age.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For girls whose puberty starts before the age of 7 years and who may reach menarche by the age of 9 years, this concern is appropriate and should be addressed. However, when puberty starts at close to the age of 8 years and is not suppressed, menarche usually does not occur until the age of 10 years or later, as US studies indicate that it takes 2.4–3 years to progress from thelarche to menarche [27, 28]. How strong is the evidence that girls having menarche close to 10 years of age experience significant distress and, if so, benefit from GnRHa treatment designed to delay menarche until the age of 11 years or later?…”
Section: Is the Prevention Of Potential Early Menarche In Girls With mentioning
confidence: 99%
“…One possible explanation for puberty not predicting SEL profile is that although the sample was primarily 5 th graders, they were further along in puberty that what has been suggested by previous literature (e.g. Cabrera, Bright, Frane, Blethen, & Lee, 2014;Herman-Giddens et al, 2012). Another possible explanation for this finding is that there was not enough variation of pubertal status in the sample.…”
Section: Prediction Of Profile Membershipmentioning
confidence: 77%